THE INFLUENCE OF THE GOVERNMENT'S INTERNAL CONTROL SYSTEM AND THE USE OF ACCOUNTING INFORMATION SYSTEMS ON THE QUALITY OF FINANCIAL REPORTS (AN EMPIRICAL STUDY ON THE RADIO FREQUENCY SPECTRUM MONITORING UNIT OF DIRECTORATE GENERAL OF RESOURCES AND EQUIPME - Syahriyani, Syahriyani; Mattulada, Andi; Fattah, Vitayanti (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research aims to determine the effect of the Government's Internal Control System and the Use of Accounting Information Systems on the Quality of Financial Reports. The samples were taken through the saturated sampling (census) technique, a sampling technique from all population members, as many as 70 respondents. The data used are quantitative and qualitative, and the data sources used are secondary and primary data. The data analysis used in this research is multiple regression analysis. Based on statistical tests on the Government's Internal Control System and the use of Accounting Information Systems, it influences the quality of financial reports at the office of Radio Frequency Spectrum Monitoring Unit, Directorate General of Resources and Equipment of Post and Information Technology. The Government's Internal Control System partially influences the quality of financial reports at the office of Radio Frequency Spectrum Monitoring Unit, Directorate General of Resources and Equipment of Post and Information Technology. Accounting Information Systems partially influences the quality of financial reports at the office of Radio Frequency Spectrum Monitoring Unit of the Directorate General of Resources and Equipment of Post and Information Technology. Keywords: Internal Control System, Accounting Information System, Financial Report Quality.